Validation of Brighton pediatric early warning score for predicting clinical deterioration in the emergency department - Rasikapriya Duraisamy; Jagadeesh Vanaja; Karuppiah Pandi Ayyappa Samy; Banupriya Balasubramaniam; Soundararajan Palanisamy (Indian Journal of Child Health, 2021)
Objectives: The objectives of the study were to validate the pediatric early warning score (PEWS) for predicting clinical deterioration in children attending the emergency department (ED) and its inter-rater agreement between nurses and pediatric trainees. Methods: This prospective observational study was done on patients aged 1 month–12 years attending the ED in tertiary care institute of South India, from June 2017 to June 2018. They were evaluated using PEWS at time of admission (S0) and after 1 h (S1) by both nurses and pediatric trainees. The scores were correlated with outcome. A receiver operating curve (ROC) was plotted to determine the cutoff value for PEWS in predicting deterioration. Inter-rater reliability between nurses and pediatric trainee was evaluated. Results: A total of 738 patients were included in the study. Patients admitted in pediatric intensive care unit (S0 2.623±2.075 and S1 2.024±1.592) had higher mean PEWS both at the time of admission and at 1 h, compared to patients admitted to the ward (S0 – 0.7551±1.129 and S1 – 0.5165±) (p